Effects of different freezing methods on calcium enriched papaya ( Carica papaya L.) - Lovera, Nancy Noelia (2018)
The effect of calcium impregnation on drip loss, colour, mechanical properties, sensory perception and freezing time on frozen-thawed papaya was studied, evaluating different freezing methods: cryogenic, tunnel and household freezer freezing. Osmotic dehydration as pre-treatment was also evaluated. Freezing in liquid nitrogen was considered an inappropriate method for papaya preservation due to cracking. Calcium impregnation and osmotic dehydration increased tissue firmness and decreased freezing time (freezing time for fresh, calcium impregnated and osmo-dehydrated fruit was 23, 17 and 5 min in a tunnel and 118, 83 and 60 min in a household freezer, respectively). Calcium lactate was the most effective way to protect tissue’s firmness before and after a freeze-thaw cycle (maximum stress values approx. 300–400% of the raw tissue for tunnel freezing and 260% for household freezer). Microstructure analysis showed better tissue integrity retention in papaya samples impregnated with calcium lactate than in those with calcium gluconate, after a freezing–thawing cycle, in agreement with the drip loss results. In spite of these results, consumers preferred frozen papaya without pre-treatment or impregnated with calcium gluconate.